Vivre la fin du monde, survivre à l’apocalypse : trois romans apocalyptiques, de la fiction à la réalité - Bebdika, Jean (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
In L’Apocalypse de 2030, Chroniques de la fin du monde and La Fin des temps, threenovels by French, American and Japanese authors respectively, the novelists try to hold upa mirror to the readers of our world that has become a field of ruin, not without warningthat the crisis of the present time is nothing compared to what awaits us in the decade of2030. The question of survival remains the major leitmotiv of this corpus and in particular,what will be tomorrow made of? By analyzing these works under the psychocritic method,the critic goes to the evidence that beyond their essentially anxiogenic and presentist vein,the apocalyptic fictions propose a rather anxiolytic frame, directed towards the prospectiveand the conduct to be held in this “crisis of the time”. Far from being “the riders ofthe apocalypse”, the authors of apocalyptic literature, set themselves up as prophets of thedays of doubt.